SPIRIT TAUHID DALAM MEMBANGUN GERAKAN KEMANUSIAAN - M. Asrul Pattimahu (Jurnal Studi Islam, 2020)
The effects of the spirit of monotheism. Tauhid or unfamiliarity memahaesakan God is a conception which contains the teachings of faith and a call that a man can only devote themselves to God as satau only God worthy of worship. The logical consequence of the spirit of monotheism gave birth to the conception that the worship of other than Allah is the forbidden, so the ideology-ideology such as polytheism, animsiem, dynamism which orients servitude to other than Allah is a false servitude orientation. If the wrong man devote themselves not only to God, then humans will fall into disrepute. Born later than the spirit of pure Tawheed it is a principle that would put humans so as not to oppress, not mutually mengsubordinasi, thus giving birth to the spirit of humanism in which humans have the same status.